SOSIALISASI PERBANKAN SYARIAH DAN GERAKAN PENANAMAN POHON DALAM RANGKA MENUMBUHKAN GREEN ECONOMY - Syifa Fadhliah; Elsa Ayuningtias; Purnama Putra; Arief Widyananto (Al-Ihsan: Journal of Community Development in Islamic Studies, 2022)
Islamic Financial Literacy in Indonesia in 2017 only reached 21.84%. Therefore, the growth of the Sharia Industry or Sharia Banking in Indonesia is still relatively low, and has not been able to achieve Green Economy growth and carry out tree planting movement in order to grow the Green Economy. The method used in this activity is an active participatory approach through socialization activities regarding Islamic Banking and joint tree planting activities. The results is that citizens are aware of the development of Islamic Banking in Indoneisa, and understand the importance of planting trees to proctect the environment. Thus, people who are still unfamiliar with Islamic Banking will know about it, in order to support the growth of Islamic Finance in Indonesia and the growth of the Green Economy.